2006
DOI: 10.1002/gcc.20332
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a new homozygous deletion in the tumor suppressor region at 3p12.3 reveals two novel intronic noncoding RNA genes

Abstract: Homozygous deletions or loss of heterozygosity (LOH) at human chromosome band 3p12 are consistent features of lung and other malignancies, suggesting the presence of a tumor suppressor gene(s) (TSG) at this location. Only one gene has been cloned thus far from the overlapping region deleted in lung and breast cancer cell lines U2020, NCI H2198, and HCC38. It is DUTT1 (Deleted in U Twenty Twenty), also known as ROBO1, FLJ21882, and SAX3, according to HUGO. DUTT1, the human ortholog of the fly gene ROBO, has hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…Downregulation of the ncRNAs was reported in renal cell carcinoma (66.67%, 4/6) and breast carcinoma (60%, 6/10), but their overexpression was observed in lung carcinoma (75%) (Angeloni et al 2006). Relatively lower expression of the ncRNAs than ROBO1/DUTT1 seen in both normal and HNSCC samples suggests the presence of diVerent promoters of these genes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Downregulation of the ncRNAs was reported in renal cell carcinoma (66.67%, 4/6) and breast carcinoma (60%, 6/10), but their overexpression was observed in lung carcinoma (75%) (Angeloni et al 2006). Relatively lower expression of the ncRNAs than ROBO1/DUTT1 seen in both normal and HNSCC samples suggests the presence of diVerent promoters of these genes.…”
Section: Discussionmentioning
confidence: 92%
“…Their overexpression has been seen in lung cancers whereas reduced expression in kidney and breast carcinoma indicating diVerential role of these ncRNAs in development of cancers (Angeloni et al 2006). Both transcripts were transcribed in the same direction as ROBO1/DUTT1, suggesting their product could be co-regulated and possibly related to ROBO1/ DUTT1 function.…”
Section: Introductionmentioning
confidence: 95%
“…One additional consequence of epigenetic silencing of Slit2 and Slit3 is downregulation of microRNA (miR)-218-1 and miR-218-2, which are located within intron 15 of human Slit2 and intron 14 of human Slit3 , respectively (Angeloni et al, 2006; Tie et al, 2010). This miR negatively regulates Robo1 expression in gastric, head and nasopharyngeal cancers (Alajez et al, 2011; Tie et al, 2010), but its downregulation due to Slit methylation in many tumor types provides one explanation for the observation that Robo1 appears to be infrequently silenced in the majority of tumor samples (Grone et al, 2006; Ito et al, 2006; Xu et al, 2010).…”
Section: Slit/robo: Roles In Epithelial Tumorigenesismentioning
confidence: 99%
“…Interestingly, the heterozygous deletion on intron 4 of the long ROBO1 transcript is within the homozygous deletion in the short ROBO1 transcript [NM_133631/ENST00000495273; hg17 spanning from intron 3 to intron 4 in the long transcript, converted by hg19 using Batch Coordinate ConversionliftOver tool (https://genome.ucsc.edu/cgi-bin/hgLiftOvert)] reported by Angeloni et al [27]. The authors also identified two lncRNAs on intron 4 of the long transcript (intron 2 of the short transcript) with the potential to modulate ROBO1 expression.…”
Section: Discussionmentioning
confidence: 92%